Peran Masjid Al-Lathiif Sebagai Pusat Kajian Keagamaan Gen-Z di Kota Bandung - Miftah Fariz Nur; Ramdan Saputra (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Etymologically, Masjid comes from the word “سَجَدَ” (Sajada), in Arabic meaning “prostration” or “submission” to Allah Swt, this word reflects the act of prostration, which is putting the forehead, hands, knees, and feet to the ground in respect and obedience. Historically, the term Masjid is also found in inscriptions from the 5th century BC as Masgid, meaning “Sacred Pillar” or “Place of Worship”. Thus, the Masjid has a deep meaning related to worship and devotion to God in Islam. One of the mosques that is often used as a center of religious studies for Gen-Z is the Al Lathif Mosque located on Jalan Saninten No. 2 Cihapit, Bandung Wetan District, Bandung City, West Java 40114, the form of studies conducted at the Al Lathif Mosque by labeling the study with a name that is easily accepted by Gen-Z, namely Tongkrongan Rohani Anak Muda. The purpose of writing this article is to find out and explain the role of Al Lathif Mosque as a center of religious studies for Gen-Z. This research uses the Questionnaire Method, this method is used to see how much Gen-Z people know and like the studies held at the Al Lathif Mosque.